Separable Codes for the Symmetric Multiple-Access Channel - D'yachkov, Arkadii; Polyanskii, Nikita; Shchukin, Vladislav; Vorobyev, Ilya (IEEE transactions on information theory, 2019)
A binary matrix is called an {s} - separable code for the disjunctive multiple-access channel ( disj-MAC ) if Boolean sums of sets of {s} columns are all distinct. The well-known issue of the combinatorial coding theory is to obtain upper and lower bounds on the rate of {s} -separable codes for the {disj} -MAC. In our paper, we generalize the problem and discuss upper and lower bounds on the rate of {q} -ary {s} -separable codes for the models of noiseless symmetric MAC, i.e., at each time instant the output signal of MAC is a symmetric function of its {s} input signals.